A study on indispensable palm oil based polyurethane - Syarifah Norsuhaila, Syed Mahmud; Mohamad Ashry, Jusoh; S. E., Jasim (Scientific Research Forum, 2017)
The use of polyurethane is widely used nowadays due to its applicability in various fields such as construction, insulating and coating. For the handling of environmental issues, the study has been to use natural based glycerol that is using palm oil-based glycerol in polyurethane preparation. Without using chemical substances such as catalysts and surfactants, the study would look at the basic characteristics of palm oilbased polyurethane. Keywords: polyurethane palm oil based, environmental friendly.